Odpowiedzi

2009-12-13T21:30:53+01:00
A) 8a³+(b²+6):c dla a= -1,b=-2, c=8
-8+¹⁰/₈= -⁵⁴/₈= -6,75

b) 4x-(5y²+8z³) dla x=-¼, y=0,2, z=-2
-1-(0,2+(-64)= -1-(-63,8)= 62,8

c) 3m³+2[m²-3(2m-1] dla m=⅓
¹/₉+2[¹/₉-3(-⅓)]=¹/₉+2[¹/₉+1]=¹/₉+2(¹⁰/₉)=¹/₉ + ²⁰/₉= ²¹/₉= ⁷/₃
1 5 1
Najlepsza Odpowiedź!
2009-12-13T21:33:29+01:00
A) 8a³+(b²+6):c dla a= -1,b=-2, c=8
-8+¹⁰/₈= -⁵⁴/₈= -6,75

b) 4x-(5y²+8z³) dla x=-¼, y=0,2, z=-2
-1-(0,2+(-64)= -1-(-63,8)= 62,8

c) 3m³+2[m²-3(2m-1] dla m=⅓
¹/₉+2[¹/₉-3(-⅓)]=¹/₉+2[¹/₉+1]=¹/₉+2(¹⁰/₉)=¹/₉ + ²⁰/₉= ²¹/₉= ⁷/₃
2 3 2